(untitled) (Jurnal Adabiya, 2020)
This paper examines the existence of Barus region as a port city of Muslim trade and its relation to the dynamics of politics, religion and the world economy that has developed since hundreds of years ago. Based on historiography and field research, Barus society have practiced Islamic law in their community life. However, the religious practices of Islam in this region declined during the colonization of Portuguese-Dutch. This colonialization was carried out in a long time and simultaneously with the strength of Christianization until the time of Indonesian independence. Based on this fact, the area of Barus and around Central Tapanuli in the recent times manifest as a minority Muslim.